Conformational polymorphism of the antidiabetic drug chlorpropamide - Ayala, A. P. (2011)
In this paper, the main features of Raman spectroscopy, one of the first choice methods in the study of polymorphism in pharmaceuticals, are presented taking chlorpropamide as a case of study. The antidiabetic drug chlorpropamide (1-[4- chlorobenzenesulphonyl]-3-propyl urea),which belongs to the sulfonylurea class, is known to exhibit, at least, six polymorphic phases. These forms are characterized not onlyby variations in their molecular packingbut also intheir molecular conformation. In this study, the polymorphism of chlorpropamide is discussed on the basis of Raman scattering measurements and quantum mechanical calculations. The main spectroscopic features that fingerprint the crystalline forms are correlated with the corresponding crystalline structures. Using a theoretical approach on the energy dependence of the conformers, simulated molecular torsion angles are plotted versus the formation energy,which provides a satisfactory agreement between the torsion angles at the energy minima and the experimental values observed in the different solid forms of chlorpropamide angles at the energy minima and the experimental values observed in the different solid forms of chlorpropamide angles at the energy minima and the experimental values observed in the different solid forms of chlorpropamide versus the formation energy,which provides a satisfactory agreement between the torsion angles at the energy minima and the experimental values observed in the different solid forms of chlorpropamide.